Apropriações didáticas das categorias do pensamento geográfico paisagem e região, no ensino fundamental brasileiro (Minas Gerais, 1971-2010) - Renato Frade da Costa (2018)
School Geography, like other disciplines, has categories of analysis that, when appropriated in a specific way, become an important didactic instrument or resource capable of attributing singularity to its object of study, the Geographic Space. This dissertation proposes to analyze how the geographical categories Landscape and Region were appropriate in the final years of Elementary School in a historical cut that covers from the year 1971 until the beginning of the year 2000. Thus we can understand, in a period of great changes in the scope of this science, the forms of performance of these categories in School Geography. The period analyzed reflects political and educational changes that contributed to different trends of thought based on new theoretical, methodological and ideological conceptions in Geography that started to dispute space in School Geography, marking the beginning of conceptual pluralism in this area of knowledge. Under the design of these trends, the categories Landscape and Region assume new characteristics that contribute to increase their presence in geographic studies. The categories studied were analyzed from different sources linked to the educational environment, whether curricular, composed of laws, programs, educational parameters and guidelines, didactic such as books used in the classroom or related to teaching practices verified in interviews conducted with professors and professors of Geography who taught for Elementary School in different moments of the studied historical cut. The sources were analyzed based on the ideals of school discipline and curriculum proposed by Ivor Goodson, that is, understood as the result of a set of forces among which stand out the public power, the academic environment, specialists in education, the teachers and other members of the school community. In order to deal with the presence of the Landscape and Region categories in School Geography, the concept of Appropriation used by Roger Chartier was adopted in his work "Cultural history. Between Practices and Representations, "in which he refers to the social history of uses and interpretations, centered on social, institutional, cultural determinations, among others, the fruit of different interests and inscribed in the specific practices that produce them. In general, it was verified that there was a relation between the three types of sources used in the development of Landscape and Region as categories of analysis of the School Geography, in order to overcome its teaching of national and generic form, until reaching the conceptual and methodological development that allow to be broadly appropriate in the geographical education process. However, aspects of the appropriation of these categories that refer to the geography prevalent at the beginning of the period studied are still present in the school environment.